Distinct Immune Response in Two MERS-CoV-Infected Patients: Can We Go from Bench to Bedside? - Faure, Emmanuel (Public Library of Science, 2014)
One year after the occurrence of the first case of infection by the Middle East Respiratory Syndrome coronavirus (MERS-CoV) there is no clear consensus on the best treatment to propose. The World Health Organization, as well as several other national agencies, are still working on different clinical approaches to implement the most relevant treatment in MERS-CoV infection. We compared innate and adaptive immune responses of two patients infected with MERS-CoV to understand the underlying mechanisms involved in the response and propose potential therapeutic approaches. Broncho-alveolar lavage (BAL) of the first week and sera of the first month from the two patients were used in this study. Quantitative polymerase chain reaction (qRTPCR) was performed after extraction of RNA from BAL cells of MERS-CoV infected patients and control patients. BAL supernatants and sera were used to assess cytokines and chemokines secretion by enzyme-linked immunosorbent assay. The first patient died rapidly after 3 weeks in the intensive care unit, the second patient still recovers from infection. The patient with a poor outcome (patient 1), compared to patient 2, did not promote type-1 Interferon (IFN), and particularly IFNα, in response to double stranded RNA (dsRNA) from MERS-CoV. The absence of IFNα, known to promote antigen presentation in response to viruses, impairs the development of a robust antiviral adaptive Th-1 immune response. This response is mediated by IL-12 and IFNγ that decreases viral clearance; levels of both of these mediators were decreased in patient 1. Finally, we confirm previous in vitro findings that MERS-CoV can drive IL-17 production in humans. Host recognition of viral dsRNA determines outcome in the early stage of MERS-CoV infection. We highlight the critical role of IFNα in this initial stage to orchestrate a robust immune response and bring substantial arguments for the indication of early IFNα treatment during MERS-CoV infection.